On The Acquisition of Tense and Aspect in Croatian - Žic Fuchs, Milena; Kačić, Miro; Kovačević, Melita (1996)
Research on the acquisition of tense and aspect in Croatian children was presented. Special emphasis was put on the possible theoretical explications of how tense and aspect are acquired by Slavic speaking children.
Projekt MZOS
ENG